PENGARUH KEPEMILIKAN KELUARGA DAN KEPEMILIKAN INSTITUSIONAL TERHADAP BIAYA KEAGENAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dona, Dona; Makhdalena, Makhdalena; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on family ownership, institutional ownership and agency costs has been largely undertaken by previous researchers, but the results have not been consistent, ie there are those who have influence and some who have no influence and some have a positive influence and some others are negatively affected. Thus, researchers are interested in re-examining family ownership and institutional ownership of agency costs. The purpose of this study was to examine and analyze the effect of family ownership and institutional ownership on agency costs. The population of this study is a manufacturing company listing on the Indonesia Stock Exchange which has complete data on family ownership, institutional ownership and agency costs for three consecutive years (2012-2014). The type of data of this research variable is secondary data obtained by documentation technique which sourced from website Bursa Efek Indonesia (www.idx.co.id). Methods of data analysis using regression. The results showed that both simultaneously and partially family ownership and institutional ownership had no effect on agency costs.Keywords: Family Ownership, Institutional Ownership, Agency Costs